Multi-Layered Metamaterial Absorber: Electromagnetic and Thermal Characterization - Bui Xuan Khuyen; Ngo Nhu Viet; Pham Thanh Son; Bui Huu Nguyen; Nguyen Hai Anh; Do Thuy Chi; Nguyen Phon Hai; Bui Son Tung; Vu Dinh Lam; Haiyu Zheng; Liangyao Chen; Youngpak Lee (Photonics, 2024)
Metamaterials, recognized as advanced artificial materials endowed with distinctive properties, have found diverse applications in everyday life, military endeavors, and scientific research. Starting from monolayer metamaterials, multilayer ones are increasingly researched, especially in the field of electromagnetic wave absorption. In this article, we propose a multilayer metamaterial-absorber (MA) structure comprising two resonant layers crafted with copper and FR-4 dielectric. The presented multilayer MA structure exhibited an absorption greater than 90% in a frequency range from 4.84 to 5.02 GHz, with two maximum absorption peaks at 4.89 and 4.97 GHz. The bandwidth of the multilayer MA surpassed that of the individual single-layer MAs, with extension fractions reaching 360% and 257%, respectively. Through the simulation and calculation, the field distribution and equivalent circuit model elucidated that both individual magnetic resonances and their interplay contribute significantly to the absorption behavior of the multilayer MA. The absorption of the proposed multilayer MA structure was also investigated for the oblique incidence in the transverse electric (TE) and transverse magnetic (TM) modes. In the TE mode, the absorption intensity of two maximum peaks was maintained at over 93% up to an incident angle of 40 degrees and dropped to below 80% at an incident angle of 60 degrees. In the TM mode, the absorption was more stable and not significantly affected by the incident angle, ranging from 0 to 60 degrees. An absorption greater than 97% was observed when the incident angle increased from 0 to 60 degrees in the TM mode. Additionally, the approach in our work was further demonstrated by adding more resonant layers, making 3- and 4-layer structures. The results indicated that the absorption bandwidths of the 3- and 4-layer structures increased by 16% and 33%, respectively, compared to the bilayer structure. Furthermore, we analyzed the thermal distribution within the MA to understand the dissipation of absorbed electromagnetic energy. This research offers valuable insight into the augmented MA through a multilayer structure, presenting the implications for microwave applications like electromagnetic shielding, as well as in the design of MAs for terahertz devices and technologies, including emission and thermal imaging. These findings contribute to the advancement of knowledge in enhancing the absorption capabilities across various frequency ranges, expanding the potential applications of metamaterials.